factor completely the given polynomial 18x^2+51x+36

## factor completely the given polynomial 18x^2+51x+36

# 2 Answers

There is the universal formula to factorize the quadratic expression: ax^{ 2}+ bx + c = a(x - x_{1})(x - x_{2}) , where x_{1} and x_{2} are roots of quadratic equation ax^{2}+ bx + c = 0 . To find the roots
we can use the formula x = (-b ± √D)/2a , where D = b^{2} - 4ac . There are 2 roots if D>0 , there is 1root if D=0 , and zero roots in set of real numbers if D is negative.

~~~~~~~~~~~~~

Let's start by taking 3 (common factor of 18, 51 and 36) out of parentheses **
18x ^{2} + 51x + 36** = 3(6x

^{2}+ 17x + 12) .... (1) and find the roots of equation 6x

^{2}+ 17x + 12 = 0 .... (2) ------> D = 17

^{2}- 4 · 6 · 12 = 1

x

_{1,2}= (-17 ± √1)/(2 · 6) = (-17 ± 1)/12 -----> x

_{1}= (-17 + 1)/12 = - 16/12 = -4/3

x

_{2}= (-17 - 1)/12 = - 18/12 = -3/2

6x2+ 17x + 12 = 6(x -(-4/3))(x - (-3/2)) = (3x + 4)(2x + 3)

The final answer will be

**3(3x + 4)(2x + 3)**

First, it looks like we can pull a 3 out of each term:

3 (6x^{2} + 17x + 12)

now we need to examine the factors of the coefficents:

6x^{2} = 1x and 6x or 2x and 3 x

12 = 1 and 12, 2 and 6, 3 and 4

Since we need the middle term to be odd, **3(2x + 3)(3x + 4)** looks like our best combination.

Check by FOIL:

3(2x + 3)(3x + 4) = 3(6x^{2} + 8x + 9x + 12) = 3 (6x^{2} + 17x + 12) =
**18x ^{2} + 51x + 36** checked!